Super-amphiphobic anti-wax precipitation epoxy composite coating as well as preparation method and application thereof
By using ultra-double anti-knot wax epoxy composite coating in oil conveying pipelines, the problems of poor stability and short service life of the coating material are solved, high mechanical strength, wear resistance and thermal stability are achieved, and the protection is significantly improved Wax properties.
Patent Information
- Application Number
- CN202411301497.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-18
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-18
AI Technical Summary
In the prior art, the coating materials have poor stability and short service life, which makes it difficult to effectively solve the problem of paraffin deposition in petroleum transport pipelines.
The preparation method of ultra-double anti-knot wax epoxy composite coating is adopted to form a modified ring by combining fluorine-containing silane modifier with nanosilia, pentaerythritol thiopropionate, propyl epoxy propyl methacrylate and other materials. An oxygen resin, and a curing agent, a catalyst and a leveling agent are added to produce a composite material with low surface energy and micro-nano structure.
It significantly improves the mechanical strength, wear resistance and thermal stability of the coating, extends service life, and maintains stability at extreme temperatures, significantly improving the anti-wax performance.
Smart Images

Figure CN119119826A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coating material development, and relates to a super-amphiphobic anti-waxing epoxy composite coating, and a preparation method and application thereof. Background Art
[0002] Crude oil is called the blood of industry. It is a very important industrial material and is widely used in energy, synthesis and many other fields. Crude oil has a high wax content, generally higher than 20%, and even up to 40%. Wax deposition is usually caused by temperature changes during oil production. During crude oil extraction and transportation, heat will be dissipated into the surrounding environment. When the temperature of crude oil drops to the wax precipitation point, the paraffin in the oil begins to crystallize, precipitate, aggregate, and deposit around the well wall or on the surface of the pipeline, thereby reducing oil production, causing considerable economic losses, and even causing potential safety problems for oil production. Therefore, mastering the characteristics of paraffin deposition and developing the best wax removal and prevention measures are of great significance to ensure safe crude oil production and reduce operating energy consumption.
[0003] At present, people have developed many methods for wax removal and prevention, among which the wax prevention coating technology has the advantages of low cost, high efficiency and wide application range, and is an ideal wax prevention strategy. Chinese patent CN201510396002.1 provides a "oil gel coating for oil pipeline anti-waxing and its coating preparation method", which applies oil gel to the oil pipeline to form a coating. The oil gel coating can absorb small molecular components in the petroleum and form a lubricating layer on the inner wall of the pipeline, thereby reducing the adhesion between the paraffin precipitated from the petroleum and the inner wall of the pipeline, which can greatly reduce the waxing phenomenon on the inner wall of the pipeline. However, due to the low mechanical strength of the gel itself, the stability and service life of its coating are poor. Chinese patent CN202011227327.4 discloses "a bionic oil pipeline coating and its preparation method", which uses the body surface of the classic pufferfish as the basic research model to prepare a hydrophilic and oleophobic oil pipeline coating with good anti-waxing effect. However, during long-term contact, petroleum will destroy the water film, causing surface contamination of the coating, thereby reducing its stability. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a super-amphiphobic anti-waxing epoxy composite coating and a preparation method and application thereof, thereby solving the technical problems of poor stability and short service life of coating materials in the prior art.
[0005] The present invention is achieved through the following technical solutions:
[0006] A method for preparing a super-amphiphobic anti-waxing epoxy composite coating comprises the following steps:
[0007] The fluorine-containing silane modifier is mixed with an alcohol aqueous solution for hydrolysis reaction to obtain a hydrolysis solution of the fluorine-containing silane modifier, and the nano-silicon dioxide dispersion is added to the hydrolysis solution of the fluorine-containing silane modifier, and the mixture is stirred for reaction to obtain the fluorine-containing silane-modified nano-silicon dioxide;
[0008] Dispersing pentaerythritol mercaptopropionate, glycidyl methacrylate and a fluorine-containing modifier with a double bond in acetone, performing ultrasonic dispersion, continuously adding a photoinitiator, stirring and dispersing the mixture uniformly, placing the reaction system under ultraviolet light, stirring and reacting the mixture to obtain a fluorine-containing modifier with an epoxy group, and uniformly mixing the fluorine-containing modifier with an epoxy group with an epoxy resin to obtain a modified epoxy resin;
[0009] After the modified epoxy resin and the fluorine-containing silane-modified nano-silica are mixed, a curing agent, a catalyst and a leveling agent are added, and the mixture is stirred evenly to obtain the super-amphiphobic anti-waxing epoxy composite material.
[0010] Preferably, the particle size of the nano-silicon dioxide is 15 to 500 nm.
[0011] Preferably, during the hydrolysis reaction, the reaction temperature is 20-30° C. and the reaction time is 1-2 h.
[0012] Preferably, the fluorine-containing silane modifier is mixed with an alcohol aqueous solution to carry out a hydrolysis reaction, and after the nano-silicon dioxide is added, the mixture is stirred and reacted at 40 to 60° C. for 4 to 8 hours.
[0013] Preferably, the ratio of the nano-silica particles to the fluorine-containing silane modifier is (0.5-5):(0.1-1) in parts by mass.
[0014] Preferably, in parts by mass, the ratio of pentaerythritol mercaptopropionate, glycidyl methacrylate and the fluorine-containing modifier with a double bond is (10-20):(10-60):(10-60).
[0015] Preferably, the ratio of the fluorine-containing modifier with epoxy group to the epoxy resin is (0.1-1):(0.4-4) in parts by mass.
[0016] Preferably, in parts by mass, the ratio of the modified epoxy resin, fluorinated silane-modified silica, curing agent, catalyst and leveling agent is (10-20):(3-10):(8-16):(0.02-0.04):(0.1-0.3).
[0017] A super-amphiphobic anti-waxing epoxy composite coating is prepared by the above method.
[0018] The above-mentioned super-amphiphobic anti-wax epoxy composite coating is used in oil pipelines.
[0019] Compared with the prior art, the present invention has the following beneficial technical effects:
[0020] The invention discloses a preparation method of a super-amphiphobic anti-waxing epoxy composite coating. Firstly, a fluorine-containing silane modifier is used to modify the surface of nano-silica to obtain fluorine-containing silane-modified nano-silica. This process not only reduces the surface energy of silica, but also enhances its compatibility with epoxy resin. Secondly, pentaerythritol mercaptopropionate, glycidyl methacrylate, a double-bonded fluorine-containing modifier and a photoinitiator are reacted to generate a fluorine-containing modifier with an epoxy group. The modifier can undergo a cross-linking reaction with the epoxy resin to obtain a modified epoxy resin with extremely low surface energy. The fluorine-containing modifier with an epoxy group is blended with the epoxy resin to ensure good compatibility between the two while giving the resin system an extremely low surface energy, so that the resin system maintains good adhesion, water resistance and corrosion resistance. Finally, the modified epoxy resin is mixed with the fluorine-containing silane-modified nano-silica, and a curing agent, a catalyst and a leveling agent are added, and the final super-amphiphobic anti-waxing epoxy composite material is obtained by stirring evenly. ; The addition of hydrophobically modified nanoparticles in this process not only further reduces the surface energy of the coating, but also enhances the super-amphiphobic performance of the coating through its micro-nano structure. The fluorinated silane-modified nano-silica is added to the epoxy resin as a filler, which significantly improves the mechanical strength, hardness and wear resistance of the epoxy resin, and improves the thermal stability of the epoxy resin, reduces the thermal expansion coefficient, and enables the material to maintain good stability and durability at extreme temperatures; In summary, the present invention reduces the surface energy of the fluorinated epoxy resin, and introduces fluorinated silane-modified SiO2 nanoparticles to further reduce the surface energy of its epoxy composite material, while constructing a micro-nano rough structure on the surface of its coating, and improving the mechanical properties of its material, utilizing the low surface energy and the "air film" effect formed, thereby developing a super-amphiphobic epoxy resin-based anti-wax coating with low surface energy and micro-nano rough structure, good stability and excellent mechanical properties. The coating has excellent hydrophobicity and oleophobicity, and can significantly improve the anti-waxing performance of the substrate.
[0021] Furthermore, the particle size of the nano-silica is 15 to 500 nm. First, the smaller the particle size of the nano-silica, the larger its specific surface area. The increase in specific surface area is conducive to improving the reactivity and adsorption capacity of the material, so that it can combine with more surface modifiers; secondly, the small particle size and good dispersibility of the nano-silica help it to be evenly mixed with other materials, thereby improving the overall performance of the composite material; finally, this size helps to construct a micro-nano rough surface structure, further improving the hydrophobic and oleophobic properties of the material.
[0022] Furthermore, during the hydrolysis reaction, the reaction temperature is 20-30°C and the reaction time is 1-2h. This temperature range helps to maintain the stability of the reaction system. Although high temperature can accelerate the reaction rate, it will also lead to an increase in side reactions or decomposition of the product, while low temperature may slow down the reaction rate, which is not conducive to production efficiency. The reaction time of 1-2 hours is sufficient for the reactants to fully contact and undergo a hydrolysis reaction, while avoiding product degradation or impurity generation that may be caused by a long reaction time. Under suitable temperature and time conditions, the hydrolysis reaction can be carried out more efficiently, thereby increasing the yield of the product.
[0023] Furthermore, the fluorinated silane modifier is mixed with an alcohol aqueous solution for a hydrolysis reaction, and after the nano-silica is added, the reaction is stirred at 40 to 60° C. for 4 to 8 hours. First, the temperature range is conducive to the chemical reaction between the fluorinated silane modifier and the nano-silica, and can ensure that the reaction proceeds at an appropriate rate while avoiding side reactions or product degradation that may be caused by high temperature. The stirring reaction time of 4 to 8 hours ensures sufficient contact and reaction between the reactants, and sufficient time allows the fluorinated silane to evenly cover the surface of the nano-silica to form a stable modified layer. Secondly, the introduction of fluorinated silane can significantly reduce the surface energy of nano-silica, making it more hydrophobic and oleophobic. This modification effect is crucial to improving the super-amphiphobic properties of the coating. At the same time, the dispersibility of the modified nano-silica in the resin will be improved, which will help reduce agglomeration and improve the uniformity and stability of the coating. Finally, the introduction of nano-silica can enhance the mechanical strength, hardness and wear resistance of the coating. After modification with fluorinated silane, these properties will be further improved, making the coating more durable when subjected to external impact and wear.
[0024] Furthermore, in terms of mass fraction, the ratio of the nano-silica particles to the fluorinated silane modifier is (0.5-5):(0.1-1). First, by adjusting the ratio of the nano-silica particles to the fluorinated silane modifier, the coverage and distribution of the modifier on the surface of the nano-particles can be accurately controlled, which helps to achieve different degrees of surface modification effects and meet the needs of different application scenarios; secondly, an appropriate amount of fluorinated silane modifier can ensure that a uniform and dense modified layer is formed on the surface of the nano-silica particles, which can not only improve the dispersibility and stability of the nano-particles, but also significantly improve their hydrophobic and oleophobic properties; finally, too much modifier may cause the modified layer to be too thick, affecting the original properties of the nano-particles, while too little modifier may fail to form an effective modified layer and fail to achieve the expected modification effect.
[0025] Furthermore, in terms of mass fractions, the ratio of pentaerythritol mercaptopropionate, glycidyl methacrylate and double-bonded fluorine-containing modifier is (10-20):(10-60):(10-60). First, pentaerythritol mercaptopropionate provides cross-linking points and enhances reactivity with other components. Its appropriate addition helps to improve the overall strength and durability of the material; glycidyl methacrylate can bring good adhesion and weather resistance to the material; the fluorine-containing group on the double-bonded fluorine-containing modifier gives the material excellent hydrophobic and oleophobic properties, and the presence of the double bond enables it to participate in the polymerization reaction and enhance the intermolecular bonding force; secondly, this ratio setting enables the final product to have a variety of excellent properties, such as high strength, good weather resistance, excellent hydrophobic and oleophobic properties, etc.; finally, the appropriate ratio helps to evenly mix the components during the reaction and reduce the reaction unevenness caused by excessively high or low local concentrations, which helps to improve the uniformity and stability of the product.
[0026] Furthermore, in terms of mass fractions, the ratio of the fluorine-containing modifier with an epoxy group to the epoxy resin is (0.1-1):(0.4-4). First, the fluorine element in the fluorine-containing modifier with an epoxy group can give the material excellent hydrophobic and oleophobic properties, which is of great significance for improving the material's stain resistance, self-cleaning and weather resistance. At the same time, the epoxy group can undergo a cross-linking reaction with the epoxy resin to further enhance the surface properties of the material. Secondly, adding an appropriate amount of the fluorine-containing modifier to the epoxy resin can increase the cross-linking density without significantly reducing the original properties of the epoxy resin, which helps to improve the material's mechanical strength, heat resistance and chemical corrosion resistance.
[0027] Furthermore, in terms of mass fractions, the ratio of the modified epoxy resin, fluorinated silane-modified silica, curing agent, catalyst and leveling agent is (10-20):(3-10):(8-16):(0.02-0.04):(0.1-0.3). Firstly, as a matrix material, the modified epoxy resin provides good mechanical properties and chemical stability, and its ratio range ensures the basic performance of the formula; the fluorinated silane-modified silica not only enhances the mechanical strength of the material, but also gives the material excellent hydrophobic and oleophobic properties through the modification of the fluorinated silane. It improves weather resistance and stain resistance; an appropriate amount of curing agent ensures that the epoxy resin can be completely cured under appropriate conditions to form a stable cross-linked network; a small amount of catalyst accelerates the curing reaction, shortens the production cycle, and ensures the uniformity and completeness of the curing reaction; an appropriate amount of leveling agent improves the fluidity and wettability of the coating, which helps to form a smooth and uniform coating during the coating process; secondly, by adjusting the proportion of each component within a reasonable range, the production cost can be minimized while ensuring product performance, which is of great significance for improving the market competitiveness of the product.
[0028] At the same time, the present invention also discloses a super-amphiphobic anti-waxing epoxy composite coating prepared by the above method. The epoxy composite coating obtained by the composite coating not only has good super-amphiphobic performance (water contact angle can reach ≥172°, glycerol contact angle can reach ≥159°, butanediol contact angle can reach ≥155°, rolling angle is less than 5°, diesel contact angle can reach ≥152°), but also has excellent acid and alkali resistance, and can be immersed in different pH solutions for 24 hours and still achieve super-amphiphobicity. Therefore, the coating has excellent corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 A schematic flow chart of a method for preparing a super-amphiphobic anti-waxing epoxy composite coating according to the present invention;
[0031] Figure 2 The contact angle test results of the super-amphiphobic anti-waxing epoxy composite coating surface prepared in Embodiment 1 of the present invention with solutions of different pH values (pH values are 3, 5, 7, 9, and 11, respectively);
[0032] Figure 3 The following are appearance pictures of coatings prepared by using E54 (pure epoxy resin), F-EP (modified epoxy resin) prepared by the present invention, and super-amphiphobic anti-waxing epoxy composite materials before and after 1260 hours of salt spray test. DETAILED DESCRIPTION
[0033] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0034] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0035] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0036] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0037] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0038] like Figure 1 As shown, the present invention provides a method for preparing a super-amphiphobic anti-waxing epoxy composite coating, comprising the following steps:
[0039] S1: mixing a fluorine-containing silane modifier with an alcohol aqueous solution for hydrolysis reaction to obtain a hydrolysis solution of the fluorine-containing silane modifier, adding a nano-silica dispersion to the hydrolysis solution of the fluorine-containing silane modifier, stirring for reaction, and obtaining fluorine-containing silane-modified nano-silica;
[0040] Specifically: by weight, add 0.1 to 1 part of fluorine-containing silane modifier to a mixture of 10 to 20 parts of ethanol and water (mass ratio 7:2) and disperse evenly, then place in a magnetic stirrer and react at 20 to 30°C for 1 to 2 hours to obtain a hydrolysis solution of the fluorine-containing silane modifier. Next, take 0.5 to 5 parts of 15 to 500 nm SiO2 and evenly disperse in 50 to 100 parts of ethanol to obtain a SiO2 dispersion. Secondly, add the SiO2 dispersion to the hydrolysis solution of the fluorine-containing silane modifier and react in a water bath at 40 to 60°C for 4 to 8 hours. After the reaction is completed, filter and wash 3 times with anhydrous ethanol. Finally, dry under vacuum at 60°C for 3 to 5 hours to obtain fluorine-containing silane-modified nano-SiO2 (F-SiO2).
[0041] Wherein, the fluorine-containing silane modifier is one or more of perfluorodecyltriethoxysilane, perfluorooctyltriethoxysilane, and perfluorohexyltriethoxysilane;
[0042] S2: dispersing pentaerythritol mercaptopropionate, glycidyl methacrylate and a fluorine-containing modifier with a double bond in acetone, performing ultrasonic dispersion, continuously adding a photoinitiator, stirring and dispersing the mixture uniformly, placing the reaction system under ultraviolet light, stirring and reacting the mixture to obtain a fluorine-containing modifier with an epoxy group, and uniformly mixing the fluorine-containing modifier with an epoxy group with an epoxy resin to obtain a modified epoxy resin;
[0043] Specifically, by weight, 10 to 20 parts of pentaerythritol mercaptopropionate, 10 to 60 parts of glycidyl methacrylate and 10 to 60 parts of a double-bond fluorine-containing modifier are uniformly dispersed by ultrasonication in 50 to 100 parts of acetone, and 0.1 to 2 parts of a photoinitiator are added, stirred until uniformly dispersed, and irradiated under an ultraviolet lamp at 20 to 40° C. for 1 to 3 hours. The product is subjected to rotary evaporation to remove the acetone solvent to obtain a fluorine-containing modifier with an epoxy group. Then, 5 to 10 parts of the fluorine-containing modifier with an epoxy group are mixed with 5 to 40 parts of an epoxy resin to obtain a modified epoxy resin.
[0044] Wherein, the double-bond fluorine-containing modifier is one or more of perfluorodecyl acrylate, tridecafluorooctyl methacrylate, tridecafluorooctyl acrylate, perfluoroalkyl methacrylate, and perfluoroalkyl vinyl ether;
[0045] The photoinitiator is one or more of 2,2-bismethoxy-2-phenylacetophenone, 4-methylbenzophenone, and 2-hydroxy-2-methyl-1-phenyl-1-propanone;
[0046] The epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, and polyphenol glycidyl ether epoxy resin;
[0047] S3: After mixing the modified epoxy resin with the fluorine-containing silane-modified nano-silica, a curing agent, a catalyst and a leveling agent are added, and the mixture is stirred evenly to obtain the super-amphiphobic anti-waxing epoxy composite material.
[0048] Specifically, first, by weight, 10 to 20 parts of modified epoxy resin are dispersed in 20 to 50 parts of ethanol, and then 3 to 10 parts of fluorinated silane-modified silica are added and stirred for 10 to 40 minutes. Next, 8 to 16 parts of curing agent, 0.02 to 0.04 parts of catalyst and 0.1 to 0.3 parts of leveling agent are added and stirred evenly to obtain a super-amphiphobic anti-waxing epoxy composite coating.
[0049] Among them, the epoxy resin is one or more of bisphenol A epoxy resin, bisphenol F epoxy resin, and polyphenol glycidyl ether epoxy resin; the curing agent is one or more of methyltetrahydrophthalic anhydride, polyamide 651, low molecular weight polyamide T31, 1,6-hexanediamine, and maleic anhydride; the catalyst is one or more of tetrabutylammonium chloride, tetrabutylammonium bromide, DMP-30 (2,4,6-tris(dimethylaminomethyl)phenol), and 2-ethyl-4-methylimidazole; the leveling agent is one or more of GD210 (purchased from Guangzhou Xinguan Chemical Technology Co., Ltd.), SRE-3450A (purchased from Guangzhou Dongfugui Chemical Raw Materials Co., Ltd.), and SKY (purchased from Kain Chemical Technology Co., Ltd.).
[0050] When the coating is used, it is sprayed on the surface of the substrate by spraying method, and the thickness of the sprayed coating is about 20μm. After curing, a super-amphiphobic anti-waxing epoxy composite coating can be obtained. The curing process adopts gradient temperature increase and is cured in the range of 60 to 170°C.
[0051] After testing, the water and diesel contact angles of the epoxy composite coating prepared by the present invention are greater than 150°, and the rolling angle is less than 5°. It can be seen that the epoxy composite coating has super-amphiphobic properties. At the same time, the anti-waxing efficiency is ≥75%. Even after a series of wear and tear, the contact angle changes very little and the super-amphiphobic performance is not lost. Even under strong acid and strong alkali conditions (pH range 1 to 14), it still has good super-amphiphobic properties. At the same time, according to the national standard GB / T-9286-2021, the adhesion of the coating is less than level 1, and the salt spray resistance time is greater than 1200h.
[0052] The calculation of anti-waxing efficiency is as follows:
[0053]
[0054] Wherein, w1 is the wax deposition amount without coating, and w2 is the wax deposition amount after coating.
[0055] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0056] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0057] Example 1
[0058] 1) Fluorosilane-modified nano-silica
[0059] First, add 0.1 parts of perfluorooctyl triethoxysilane to 10 parts of ethanol-water mixture and disperse evenly, then place in a magnetic stirrer and react at 25°C for 1 hour to obtain a hydrolysis solution of fluorinated silane modifier. Next, take 0.5 parts of 100nm SiO2 and disperse it evenly in 50 parts of ethanol to obtain SiO2 dispersion. Secondly, add the dispersed nano-SiO2 to the hydrolyzed solution and place in a water bath at 40°C for 8 hours. After the reaction is completed, filter and wash with anhydrous ethanol. Finally, dry under vacuum at 60°C for 5 hours to obtain fluorinated silane-modified SiO2 (F-SiO2).
[0060] 2) Preparation of modified epoxy resin
[0061] 10 parts of pentaerythritol mercaptopropionate, 20 parts of glycidyl methacrylate and 20 parts of tridecafluorooctyl acrylate were ultrasonically dispersed in 50 parts of acetone, and 0.1 parts of 2,2-bismethoxy-2-phenylpropiophenone were added, stirred until uniformly dispersed, and illuminated under ultraviolet light at 25°C for 2 hours. The product was subjected to rotary evaporation to remove the acetone solvent to obtain a fluorine-containing modifier with epoxy groups. Then 5 parts of the fluorine-containing epoxy resin modifier were mixed with 10 parts of bisphenol A epoxy resin to obtain a modified epoxy resin.
[0062] 3) Preparation of super-amphiphobic anti-wax epoxy composite coating
[0063] Disperse 10 parts of modified epoxy resin in 20 parts of ethanol, add 3 parts of fluorinated silane-modified silica and stir for 30 minutes. Then, add 8 parts of methyltetrahydrophthalic anhydride, 0.02 parts of tetrabutylammonium chloride and 0.1 parts of GD210 and stir evenly. Finally, the super-amphiphobic anti-waxing epoxy composite coating is prepared by spraying on the surface of the metal steel plate. The curing process is: 120℃ / 4min+130℃ / 5min+140℃ / 6min+150℃ / 7min+170℃ / 30min.
[0064] The super-amphiphobic anti-waxing epoxy composite coating prepared in this embodiment has a water contact angle of 172°, a diesel contact angle of 152° (rolling angle 4°), an anti-waxing rate of 75%, a coating adhesion of level 0, and a salt spray resistance time of 1260h.
[0065] Example 2
[0066] 1) Fluorosilane-modified nanosilica
[0067] First, add 0.5 parts of perfluorooctyl triethoxysilane to 10 parts of ethanol-water mixture and disperse evenly, then place in a magnetic stirrer and react at 21°C for 2 hours to obtain a hydrolysis solution of fluorinated silane modifier. Next, take 3 parts of 100nm SiO2 and evenly disperse them in 70 parts of ethanol to obtain a SiO2 dispersion. Secondly, add the dispersed nano-SiO2 to the hydrolysis solution of the fluorinated silane modifier and place in a water bath at 50°C for 7 hours. After the reaction is completed, filter and wash with anhydrous ethanol. Finally, dry under vacuum at 60°C for 3 hours to obtain fluorinated silane-modified SiO2 (F-SiO2).
[0068] 2) Preparation of modified epoxy resin
[0069] 10 parts of pentaerythritol mercaptopropionate, 20 parts of glycidyl methacrylate and 20 parts of tridecafluorooctyl acrylate were uniformly dispersed by ultrasonication in 50 parts of acetone, and 0.1 parts of 2,2-bismethoxy-2-phenylpropiophenone were added, stirred until uniformly dispersed, and illuminated at 30°C under ultraviolet light for 1.5 hours. The product was subjected to rotary evaporation to remove the acetone solvent to obtain a fluorine-containing modifier with epoxy groups. Then 5 parts of the fluorine-containing epoxy resin modifier were mixed with 10 parts of bisphenol A epoxy resin to obtain a modified epoxy resin.
[0070] 3) Preparation of super-amphiphobic anti-wax epoxy composite coating
[0071] Disperse 10 parts of modified epoxy resin in 20 parts of ethanol, add 4 parts of fluorinated silane-modified silica and stir for 30 minutes. Then, add 8 parts of methyltetrahydrophthalic anhydride, 0.02 parts of tetrabutylammonium bromide and 0.1 parts of GD210 and stir evenly. Finally, spray the super-amphiphobic anti-waxing epoxy composite coating on the surface of the glass plate. The curing process is: 120℃ / 4min+130℃ / 5min+140℃ / 6min+150℃ / 7min+170℃ / 30min.
[0072] The super-amphiphobic anti-waxing epoxy composite coating prepared in this embodiment has a water contact angle of 173°, a diesel contact angle of 154° (rolling angle 4°), an anti-waxing rate of 79%, a coating adhesion of level 0, and a salt spray resistance time of 1308h.
[0073] Example 3
[0074] 1) Fluorosilane-modified nanosilica
[0075] First, add 1 part of perfluorooctyl triethoxysilane to 15 parts of ethanol-water mixture and disperse it evenly, then place it in a magnetic stirrer and react at 27°C for 1 hour to obtain a hydrolysis solution of the fluorinated silane modifier. Next, take 5 parts of 300nm SiO2 and evenly disperse them in 100 parts of ethanol to obtain a SiO2 dispersion. Secondly, add the dispersed nano-SiO2 to the hydrolysis solution of the fluorinated silane modifier and place it in a water bath at 60°C for 4 hours. After the reaction is completed, filter and wash with anhydrous ethanol. Finally, dry it under vacuum at 60°C for 4 hours to obtain fluorinated silane-modified SiO2 (F-SiO2).
[0076] 2) Preparation of modified epoxy resin
[0077] 10 parts of pentaerythritol mercaptopropionate, 30 parts of glycidyl methacrylate and 10 parts of perfluorodecyl acrylate were ultrasonically dispersed in 50 parts of acetone, and 0.2 parts of 2,2-bismethoxy-2-phenylpropiophenone were added, stirred until uniformly dispersed, and illuminated under ultraviolet light at 25°C for 2 hours. The product was subjected to rotary evaporation to remove the acetone solvent to obtain a fluorine-containing modifier with epoxy groups. Then 7 parts of the fluorine-containing epoxy resin modifier were mixed with 15 parts of bisphenol A epoxy resin to obtain a modified epoxy resin.
[0078] 3) Preparation of super-amphiphobic anti-wax epoxy composite coating
[0079] Disperse 15 parts of modified epoxy resin in 30 parts of ethanol, add 5 parts of fluorinated silane-modified silica and stir for 40 minutes. Then, add 6 parts of polyamide 651, 0.015 parts of DMP-30 and 0.2 parts of SKY and stir evenly. Finally, spray the super-amphiphobic anti-waxing epoxy composite coating on the surface of the wood board. The curing process is: 60℃ / 30min+70℃ / 20min+120℃ / 10min.
[0080] The super-amphiphobic anti-waxing epoxy composite coating prepared in this embodiment has a water contact angle of 175°, a diesel contact angle of 157° (rolling angle 4°), an anti-waxing rate of 89%, a coating adhesion of level 0, and a salt spray resistance time of 1674h.
[0081] Example 4
[0082] 1) Fluorosilane-modified nanosilica
[0083] First, add 0.1 parts of perfluorooctyl triethoxysilane to 10 parts of ethanol-water mixture and disperse evenly, then place in a magnetic stirrer and react at 25°C for 2 hours to obtain a hydrolysis solution of fluorinated silane modifier. Next, take 0.5 parts of 300nm SiO2 and evenly disperse it in 50 parts of ethanol to obtain a SiO2 dispersion. Secondly, add the dispersed nano-SiO2 to the hydrolysis solution of the fluorinated silane modifier and place in a water bath at 40°C for 8 hours. After the reaction is completed, filter and wash with anhydrous ethanol. Finally, dry under vacuum at 60°C for 5 hours to obtain fluorinated silane-modified SiO2 (F-SiO2).
[0084] 2) Preparation of modified epoxy resin
[0085] 10 parts of pentaerythritol mercaptopropionate, 30 parts of glycidyl methacrylate and 10 parts of perfluorodecyl acrylate were uniformly dispersed by ultrasonication in 50 parts of acetone, and 0.3 parts of 4-methylbenzophenone were added, stirred until uniformly dispersed, and illuminated at 30°C under ultraviolet light for 1.5 hours. The product was subjected to rotary evaporation to remove the acetone solvent to obtain a fluorine-containing modifier with epoxy groups. Then 7 parts of the fluorine-containing epoxy resin modifier were mixed with 15 parts of bisphenol A epoxy resin to obtain a modified epoxy resin.
[0086] 3) Preparation of super-amphiphobic anti-wax epoxy composite coating
[0087] Disperse 15 parts of modified epoxy resin in 30 parts of ethanol, add 5 parts of fluorinated silane-modified silica and stir for 40 minutes. Then, add 6 parts of low molecular weight polyamide T31, 0.015 parts of DMP-30 and 0.2 parts of SRE-3450A and stir evenly. Finally, spray the super-amphiphobic anti-waxing epoxy composite coating on the surface of the metal steel plate. The curing process is: 60℃ / 2h+100℃ / 30min.
[0088] The super-amphiphobic anti-waxing epoxy composite coating prepared in this embodiment has a water contact angle of 168°, a diesel contact angle of 151° (rolling angle 5°), an anti-waxing rate of 77%, a coating adhesion of level 0, and a salt spray resistance time of 1274h.
[0089] Example 5
[0090] 1) Fluorosilane-modified nanosilica
[0091] First, add 1 part of perfluorooctyl triethoxysilane to 15 parts of ethanol-water mixture and disperse it evenly, then place it in a magnetic stirrer and react at 27°C for 1 hour to obtain a hydrolysis solution of the fluorinated silane modifier. Next, take 5 parts of 500nm SiO2 and evenly disperse them in 100 parts of ethanol to obtain a SiO2 dispersion. Secondly, add the dispersed nano-SiO2 to the hydrolysis solution of the fluorinated silane modifier and place it in a water bath at 60°C for 4 hours. After the reaction is completed, filter and wash with anhydrous ethanol. Finally, dry it under vacuum at 60°C for 4 hours to obtain fluorinated silane-modified SiO2 (F-SiO2).
[0092] 2) Preparation of modified epoxy resin
[0093] 10 parts of pentaerythritol mercaptopropionate, 20 parts of glycidyl methacrylate and 20 parts of perfluorodecyl acrylate were ultrasonically dispersed in 50 parts of acetone, and 0.5 parts of 4-methylbenzophenone were added, stirred until uniformly dispersed, and illuminated at 40°C under ultraviolet light for 1 hour. The product was subjected to rotary evaporation to remove the acetone solvent to obtain a fluorine-containing modifier with epoxy groups. Then 5 parts of the fluorine-containing epoxy resin modifier were mixed with 10 parts of bisphenol A epoxy resin to obtain a modified epoxy resin.
[0094] 3) Preparation of super-amphiphobic anti-wax epoxy composite coating
[0095] Disperse 15 parts of modified epoxy resin in 30 parts of ethanol, add 4 parts of fluorinated silane-modified silica and stir for 40 minutes. Then, add 6 parts of low molecular weight polyamide T31, 0.015 parts of tetrabutylammonium bromide and 0.2 parts of SKY and stir evenly. Finally, spray the super-amphiphobic anti-waxing epoxy composite coating on the surface of the cement board. The curing process is: 60℃ / 2h+100℃ / 30min.
[0096] The super-amphiphobic anti-waxing epoxy composite coating prepared in this embodiment has a water contact angle of 174°, a diesel contact angle of 156° (rolling angle 3°), an anti-waxing rate of 90%, a coating adhesion of level 1, and a salt spray resistance time of 1709h.
[0097] Example 6
[0098] 1) Fluorosilane-modified nano-silica
[0099] First, add 0.5 parts of perfluorodecyltriethoxysilane to 10 parts of ethanol-water mixture and disperse evenly, then place in a magnetic stirrer and react at 21°C for 2 hours to obtain a hydrolysis solution of fluorinated silane modifier. Next, take 3 parts of 100nm SiO2 and evenly disperse them in 70 parts of ethanol to obtain a SiO2 dispersion. Secondly, add the dispersed nano-SiO2 to the hydrolysis solution of the fluorinated silane modifier and place in a water bath at 50°C for 7 hours. After the reaction is completed, filter and wash with anhydrous ethanol. Finally, dry under vacuum at 60°C for 3 hours to obtain fluorinated silane-modified SiO2 (F-SiO2).
[0100] 2) Preparation of modified epoxy resin
[0101] 10 parts of pentaerythritol mercaptopropionate, 20 parts of glycidyl methacrylate and 20 parts of perfluorodecyl acrylate were ultrasonically dispersed in 50 parts of acetone, and 1 part of 4-methylbenzophenone was added, stirred until uniformly dispersed, and illuminated at 35°C under ultraviolet light for 1 hour. The product was subjected to rotary evaporation to remove the acetone solvent to obtain a fluorine-containing modifier with epoxy groups. Then 5 parts of the fluorine-containing epoxy resin modifier were mixed with 10 parts of bisphenol F epoxy resin to obtain a modified epoxy resin.
[0102] 3) Preparation of super-amphiphobic anti-wax epoxy composite coating
[0103] Disperse 15 parts of modified epoxy resin in 30 parts of ethanol, add 6 parts of fluorinated silane-modified silica and stir for 40 minutes. Then, add 6 parts of maleic anhydride, 0.015 parts of 2-ethyl-4-methylimidazole and 0.2 parts of GD210 and stir evenly. Finally, spray the super-amphiphobic anti-waxing epoxy composite coating on the surface of the glass fiber reinforced plastic plate. The curing process is: 60℃ / 4h.
[0104] The super-amphiphobic anti-waxing epoxy composite coating prepared in this embodiment has a water contact angle of 170°, a diesel contact angle of 153° (rolling angle 5°), an anti-waxing rate of 84%, a coating adhesion of level 0, and a salt spray resistance time of 1874h.
[0105] Example 7
[0106] 1) Fluorosilane-modified nano-silica
[0107] First, add 0.1 parts of perfluorodecyltriethoxysilane to 10 parts of ethanol-water mixture and disperse evenly, then place in a magnetic stirrer and react at 25°C for 1 hour to obtain a hydrolysis solution of the fluorinated silane modifier. Next, take 0.5 parts of 300nmSiO2 and disperse it evenly in 50 parts of ethanol to obtain a SiO2 dispersion. Secondly, add the dispersed nano-SiO2 to the hydrolysis solution of the fluorinated silane modifier and place in a water bath at 40°C for 8 hours. After the reaction is completed, filter and wash with anhydrous ethanol. Finally, dry under vacuum at 60°C for 5 hours to obtain fluorinated silane-modified SiO2 (F-SiO2).
[0108] 2) Preparation of modified epoxy resin
[0109] 5 parts of pentaerythritol mercaptopropionate, 10 parts of glycidyl methacrylate and 10 parts of tridecafluorooctyl methacrylate were uniformly dispersed by ultrasonication in 25 parts of acetone, and 0.1 parts of 4-methylbenzophenone were added, stirred until uniformly dispersed, and illuminated at 30°C under ultraviolet light for 2 hours. The product was subjected to rotary evaporation to remove the acetone solvent to obtain a fluorine-containing modifier with epoxy groups. Then 5 parts of the fluorine-containing epoxy resin modifier were mixed with 10 parts of bisphenol F epoxy resin to obtain a modified epoxy resin.
[0110] 3) Preparation of super-amphiphobic anti-wax epoxy composite coating
[0111] Disperse 10 parts of modified epoxy resin in 20 parts of ethanol, add 5 parts of fluorinated silane-modified silica and stir for 40 minutes. Then, add 8 parts of 1,6-hexanediamine and 0.1 parts of GD210 and stir evenly. Finally, spray the super-amphiphobic anti-waxing epoxy composite coating on the surface of the metal steel plate. The curing process is: room temperature curing for 5 hours.
[0112] The super-amphiphobic anti-waxing epoxy composite coating prepared in this embodiment has a water contact angle of 167°, a diesel contact angle of 150° (rolling angle 5°), an anti-waxing rate of 75%, a coating adhesion of level 0, and a salt spray resistance time of 1299h.
[0113] Example 8
[0114] 1) Fluorosilane-modified nano-silica
[0115] First, add 1 part of perfluorodecyl triethoxysilane to 15 parts of ethanol-water mixture and disperse it evenly, then place it in a magnetic stirrer and react at 27°C for 1 hour to obtain a hydrolysis solution of the fluorinated silane modifier. Next, take 5 parts of 500nm SiO2 and evenly disperse them in 100 parts of ethanol to obtain a SiO2 dispersion. Secondly, add the dispersed nano-SiO2 to the hydrolysis solution of the fluorinated silane modifier and place it in a water bath at 60°C for 4 hours. After the reaction is completed, filter and wash with anhydrous ethanol. Finally, dry it under vacuum at 60°C for 4 hours to obtain fluorinated silane-modified SiO2 (F-SiO2).
[0116] 2) Preparation of modified epoxy resin
[0117] 20 parts of pentaerythritol mercaptopropionate, 60 parts of glycidyl methacrylate and 20 parts of tridecafluorooctyl methacrylate were uniformly dispersed by ultrasonication in 100 parts of acetone, and 2 parts of 4-methylbenzophenone were added, stirred until uniformly dispersed, and illuminated under ultraviolet light at 40°C for 1 hour. The product was subjected to rotary evaporation to remove the acetone solvent to obtain a fluorine-containing modifier with epoxy groups. Then 10 parts of the fluorine-containing epoxy resin modifier were mixed with 30 parts of bisphenol A epoxy resin to obtain a modified epoxy resin.
[0118] 3) Preparation of super-amphiphobic anti-wax epoxy composite coating
[0119] Disperse 10 parts of modified epoxy resin in 20 parts of ethanol, add 5 parts of fluorinated silane-modified silica and stir for 40 minutes. Then, add 8 parts of maleic anhydride, 0.02 parts of DMP-30 and 0.1 parts of SRE-3450A and stir evenly. Finally, spray the super-amphiphobic anti-waxing epoxy composite coating on the surface of the glass fiber reinforced plastic plate. The curing process is: 100℃ / 2h.
[0120] The super-amphiphobic anti-waxing epoxy composite coating prepared in this embodiment has a water contact angle of 176°, a diesel contact angle of 158° (rolling angle 3°), an anti-waxing rate of 93%, a coating adhesion of level 0, and a salt spray resistance time of 2022h.
[0121] In order to further test the stability of the super-phobic performance of the super-amphiphobic anti-waxing epoxy composite coating prepared by the present invention, the contact angle of the super-amphiphobic anti-waxing epoxy composite coating surface prepared by the embodiment 1 of the present invention was measured using solutions with different pH values (pH values were 3, 5, 7, 9, and 11, respectively). The test results are shown in FIG. Figure 2 As can be seen from the figure, the water contact angle of the super-amphiphobic anti-waxing epoxy composite coating prepared in Example 1 of the present invention in different pH solutions is greater than 150°, and the rolling angle is less than 5°, that is, the super-amphiphobic anti-waxing epoxy composite coating prepared in the present invention has good dual super-phobic (super-hydrophobic and super-oleophobic) effects in a wider pH value range and has good stability.
[0122] In addition, in order to further verify the stability of the corrosion resistance of the super-amphiphobic anti-waxing epoxy composite coating prepared by the present invention, a 1260-h salt spray test was carried out using E54 (pure epoxy resin), F-EP (modified epoxy resin) prepared in Example 1 of the present invention, and a coating prepared with a super-amphiphobic anti-waxing epoxy composite material. The degree of corrosion of the grid edge was observed before and after the salt spray test. It can be seen from the figure that the super-amphiphobic anti-waxing epoxy composite coating prepared by the present invention did not show a large amount of corrosion after 1260 hours of salt spray, and had good corrosion resistance stability.
[0123] Example 9
[0124] A method for preparing a super-amphiphobic anti-waxing epoxy composite coating comprises the following steps:
[0125] S1: In terms of mass fractions, 0.1 parts of fluorinated silane modifier was added to a mixture of 10 parts of ethanol and water (mass ratio 7:2) and dispersed evenly, and then placed in a magnetic stirrer and reacted at 20°C for 1h to obtain a hydrolysis solution of the fluorinated silane modifier. Next, 0.5 parts of 15nm SiO2 were uniformly dispersed in 50 parts of ethanol to obtain a SiO2 dispersion. Secondly, the SiO2 dispersion was added to the hydrolysis solution of the fluorinated silane modifier and reacted in a 40°C water bath for 8h. After the reaction, it was filtered and washed 3 times with anhydrous ethanol. Finally, it was dried under vacuum at 60°C for 3h to obtain fluorinated silane-modified nano-SiO2 (F-SiO2).
[0126] Wherein, the fluorinated silane modifier is perfluorodecyltriethoxysilane;
[0127] S2: By mass, 10 parts of pentaerythritol mercaptopropionate, 10 parts of glycidyl methacrylate and 10 parts of fluorine-containing modifier with double bonds are uniformly dispersed in 50 parts of acetone by ultrasonication, and 0.1 parts of photoinitiator are added, stirred until uniformly dispersed, and illuminated under ultraviolet light at 20°C for 1 hour. The product is subjected to rotary evaporation to remove the acetone solvent to obtain a fluorine-containing modifier with epoxy groups. Then 5 parts of the fluorine-containing modifier with epoxy groups are mixed with 5 parts of epoxy resin to obtain a modified epoxy resin.
[0128] The double-bond fluorine-containing modifier is a mixture of perfluorodecyl acrylate and tridecafluorooctyl methacrylate; the photoinitiator is 2,2-bismethoxy-2-phenylacetophenone; the epoxy resin is bisphenol A epoxy resin;
[0129] S3: First, by weight, 10 parts of modified epoxy resin are dispersed in 20 parts of ethanol, and then 3 to 10 parts of fluorinated silane-modified silica are added and stirred for 10 minutes. Next, 8 parts of curing agent, 0.02 parts of catalyst and 0.1 parts of leveling agent are added and stirred evenly to obtain a super-amphiphobic anti-waxing epoxy composite coating.
[0130] Wherein, the epoxy resin is bisphenol A epoxy resin; the curing agent is methyltetrahydrophthalic anhydride; and the catalyst is tetrabutylammonium chloride.
[0131] Example 10
[0132] A method for preparing a super-amphiphobic anti-waxing epoxy composite coating comprises the following steps:
[0133] S1: In parts by mass, add 1 part of fluorinated silane modifier to a mixture of 20 parts of ethanol and water (mass ratio 7:2) and disperse evenly, then place in a magnetic stirrer and react at 30°C for 1 hour to obtain a hydrolysis solution of the fluorinated silane modifier. Next, take 5 parts of 500nm SiO2 and evenly disperse them in 100 parts of ethanol to obtain a SiO2 dispersion. Secondly, add the SiO2 dispersion to the hydrolysis solution of the fluorinated silane modifier and react in a 60°C water bath for 4 hours. After the reaction, filter and wash 3 times with anhydrous ethanol. Finally, dry under vacuum at 60°C for 3 hours to obtain fluorinated silane-modified nano-SiO2 (F-SiO2). Among them, the fluorinated silane modifier is perfluorooctyltriethoxysilane;
[0134] S2: In terms of mass fractions, 20 parts of pentaerythritol mercaptopropionate, 60 parts of glycidyl methacrylate and 60 parts of fluorine-containing modifier with double bonds are uniformly dispersed by ultrasonication in 100 parts of acetone, and 2 parts of photoinitiator are added, stirred until uniformly dispersed, and illuminated at 40°C under ultraviolet lamp for 1 hour. The product is subjected to rotary evaporation to remove the acetone solvent to obtain a fluorine-containing modifier with epoxy group. Then 10 parts of the fluorine-containing modifier with epoxy group are mixed with 40 parts of epoxy resin to obtain a modified epoxy resin. Among them, the fluorine-containing modifier with double bonds is a mixture of tridecafluorooctyl acrylate, perfluoroalkyl methacrylate and perfluoroalkyl vinyl ether; the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone; the epoxy resin is bisphenol F type epoxy resin;
[0135] S3: Disperse 20 parts of modified epoxy resin in 50 parts of ethanol by mass, add 10 parts of fluorinated silane-modified silica and stir for 40 minutes. Then, add 16 parts of curing agent, 0.04 parts of catalyst and 0.3 parts of leveling agent, stir evenly, and obtain a super-amphiphobic anti-waxing epoxy composite coating. Among them, the epoxy resin is bisphenol F epoxy resin; the curing agent is a mixture of 1,6-hexanediamine and maleic anhydride; the catalyst is 2-ethyl-4-methylimidazole.
[0136] Embodiment 11
[0137] A method for preparing a super-amphiphobic anti-waxing epoxy composite coating comprises the following steps:
[0138] S1: In terms of mass fractions, add 0.5 parts of fluorinated silane modifier to a mixture of 15 parts of ethanol and water (mass ratio 7:2) and disperse evenly, then place in a magnetic stirrer and react at 25°C for 1.5 hours to obtain a hydrolysis solution of the fluorinated silane modifier. Next, take 2 parts of 200nm SiO2 and evenly disperse them in 80 parts of ethanol to obtain a SiO2 dispersion. Secondly, add the SiO2 dispersion to the hydrolysis solution of the fluorinated silane modifier and react in a 50°C water bath for 6 hours. After the reaction, filter and wash 3 times with anhydrous ethanol. Finally, dry under vacuum at 60°C for 4 hours to obtain fluorinated silane-modified nano-SiO2 (F-SiO2). Among them, the fluorinated silane modifier is perfluorohexyltriethoxysilane;
[0139] S2: In terms of mass fractions, 15 parts of pentaerythritol mercaptopropionate, 30 parts of glycidyl methacrylate and 40 parts of fluorine-containing modifier with double bonds are uniformly dispersed by ultrasonication in 80 parts of acetone, and 1.5 parts of photoinitiator are added, stirred until uniformly dispersed, and illuminated at 30°C under ultraviolet lamp for 2 hours. The product is subjected to rotary evaporation to remove the acetone solvent to obtain a fluorine-containing modifier with epoxy group. Then 8 parts of the fluorine-containing modifier with epoxy group are mixed with 20 parts of epoxy resin to obtain a modified epoxy resin. Among them, the fluorine-containing modifier with double bonds is perfluoroalkyl vinyl ether; the photoinitiator is 4-methylbenzophenone; the epoxy resin is a polyphenol-type glycidyl ether epoxy resin;
[0140] S3: Disperse 15 parts of modified epoxy resin in 30 parts of ethanol by mass, add 7 parts of fluorinated silane-modified silica and stir for 30 minutes. Then, add 15 parts of curing agent, 0.03 parts of catalyst and 0.2 parts of leveling agent, stir evenly, and obtain a super-amphiphobic anti-waxing epoxy composite coating. Among them, the epoxy resin is a polyphenol-type glycidyl ether epoxy resin; the curing agent is 1,6-hexanediamine; and the catalyst is DMP-30.
[0141] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0142] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a super-amphiphobic anti-waxing epoxy composite coating, It is characterized in that The following steps are involved: The fluorine-containing silane modifier is mixed with an alcohol aqueous solution for hydrolysis reaction to obtain a hydrolysis solution of the fluorine-containing silane modifier, and the nano-silicon dioxide dispersion is added to the hydrolysis solution of the fluorine-containing silane modifier, and the mixture is stirred for reaction to obtain the fluorine-containing silane-modified nano-silicon dioxide; Dispersing pentaerythritol mercaptopropionate, glycidyl methacrylate and a fluorine-containing modifier with a double bond in acetone, performing ultrasonic dispersion, continuously adding a photoinitiator, stirring and dispersing the mixture uniformly, placing the reaction system under ultraviolet light, stirring and reacting the mixture to obtain a fluorine-containing modifier with an epoxy group, and uniformly mixing the fluorine-containing modifier with an epoxy group with an epoxy resin to obtain a modified epoxy resin; After the modified epoxy resin and the fluorine-containing silane-modified nano-silica are mixed, a curing agent, a catalyst and a leveling agent are added, and the mixture is stirred evenly to obtain the super-amphiphobic anti-waxing epoxy composite material.
2. A method for preparing a super-amphiphobic anti-waxing epoxy composite coating according to claim 1, It is characterized in that The particle size of the nano silicon dioxide is 15 to 500 nm.
3. A method for preparing a super-amphiphobic anti-waxing epoxy composite coating according to claim 1, It is characterized in that During the hydrolysis reaction, the reaction temperature is 20-30° C. and the reaction time is 1-2 h.
4. The method for preparing a super-amphiphobic anti-waxing epoxy composite coating according to claim 1, It is characterized in that The fluorine-containing silane modifier is mixed with the alcohol aqueous solution for hydrolysis reaction, and after the nano-silicon dioxide is added, the mixture is stirred and reacted at 40-60° C. for 4-8 hours.
5. The method for preparing a super-amphiphobic anti-waxing epoxy composite coating according to claim 1, It is characterized in that Calculated by mass, the ratio of the nano-silica particles to the fluorine-containing silane modifier is (0.5-5):(0.1-1).
6. A method for preparing a super-amphiphobic anti-waxing epoxy composite coating according to claim 1, It is characterized in that In parts by mass, the ratio of pentaerythritol mercaptopropionate, glycidyl methacrylate and the double-bond fluorine-containing modifier is (10-20):(10-60):(10-60).
7. The method for preparing a super-amphiphobic anti-waxing epoxy composite coating according to claim 1, It is characterized in that In terms of mass fractions, the ratio of the fluorine-containing modifier with epoxy group to the epoxy resin is (0.1-1):(0.4-4).
8. The method for preparing a super-amphiphobic anti-waxing epoxy composite coating according to claim 1, It is characterized in that In parts by mass, the ratio of the modified epoxy resin, fluorinated silane-modified silica, curing agent, catalyst and leveling agent is (10-20):(3-10):(8-16):(0.02-0.04):(0.1-0.3).
9. A super-amphiphobic anti-waxing epoxy composite coating, It is characterized in that It is prepared by the method according to any one of claims 1 to 8.
10. Use of the super-amphiphobic anti-waxing epoxy composite coating as claimed in claim 9 in oil pipelines.
Citation Information
Patent Citations
Oil pipeline anti-waxing oil gel coating and preparation method thereof
CN104910806A
Bionic petroleum pipeline coating and preparation method thereof
CN112521813A
Case for small electrical apparatus
EP0001260A1
Stable and transparent super-hydrophobic or super-amphiphobic coating as well as preparation method and application thereof
CN103436138A
Anti-waxing coating for crude oil pipeline and coating layer preparation method
CN109423162A
Cited By
A temperature-resistant anti-wax drag-reducing pipeline inner wall coating and a preparation method thereof
CN122898192A
